Optimalisasi Program Police Goes To Factory Oleh Unit Dikyasa Satuan Lalu Lintas Kepada Karyawan Swasta Dalam Menurunkan Angka Pelanggaran Lalu Lintas Di Wilayah Hukum Polres Cianjur - Hanif, Hendon (Police Studies Review, 2020)
The traffic condition in Cianjur Regency is quite congested due to the factory activity which is located on the side of the protocol road, triggering a traffic jam that allows traffic accidents to occur on the highway. Kamseltibcar then in the Cianjur Police jurisdiction is still not created properly. Therefore, it requires public awareness and understanding, especially those who work as private employees. Prevention efforts have been made by the police in dealing with traffic violations through a public education program about traffic or called Dikmas Lantas. The purpose of this study is to describe, analyze the program implementation and the factors that influence the implementation of the Police Goes to Factory program and explain how program optimization by the unit dikyasa reduces the number of traffic violations to the community in the jurisdiction of the Cianjur Police. This type of research is a qualitative research with descriptive analysis research type. The location of this research is in the jurisdiction of Cianjur Police, where private employees are the object of this research. The data was collected using observation, interview and document study techniques and analyzed by reducing the data, presenting it and drawing conclusions. The results showed that there were some shortcomings during implementation, namely the quality and quantity of personnel, activity budgets and the intensity of the implementation of activities that were lacking. The factors that influence the implementation of the unit are human, money, completeness, market and method. To optimize the community education program then, the qualifications of personnel abilities need to be analyzed using performance theory, namely capability, clarity, support, motivation, validity and environment.